Governança corporativa, mercado de capitais e crescimento econômico no Brasil - Silva, Pablo Rogers (2006)
Relevant literature points out that the stock market development depends on setting good corporate governance practices, which, in itself, will make country development more dynamic. By adopting efficient corporate governance models we increase liquidity, negotiation volume, and valorization, also we reduce company stock volatility, therefore diminishing exposure of stock return to macro economical factors. The present paper aims at investigating the superior governance practices which reduce the exposure of stock return to macro economical factors, and to what extent these practices relate to the economical development of the company. In order to obtain such information we have conducted comparative analysis of the Corporate Governance Index (CGI; or in Portuguese IGC) and the Ibovespa (Brazilian Stock Market Index) in relation to the macro economical variables we find in the academic literature which influence the most the national stock market. In terms of methodology, we have proceeded with a descriptive research of the quantitative type where we were able to estimate models in differences through the Ordinary Least Square model (OLS), almost-difference models with Bootstrap, Non-linear models with Quasi-maximum Likelihoold (QML) and Vector Auto-Regressive (VAR) with the Variance Decomposition tool. We have concluded that the best corporate governance practices, measured according to the CGI, reduces the exposure of stock return to macro economical factors and the companies which adopt such practices have a better performance (have more benefits) in the cycle of economical growth in the companies which do not adopt that.